Effect of bed height on laryngoscopy force and operator ergonomics during simulated endotracheal intubation: A randomized controlled study - Ja Eun Lee; Kwan Young Hong; Chisong Chung; Jeong-Jin Min (PLoS ONE, 2025)
Purpose Excessive force during laryngoscopy for endotracheal intubation can result in injury to airway soft tissues and hemodynamic stress responses. In this randomized controlled trial on simulated intubation, we aimed to evaluate the effect of bed height on laryngoscopy force and operator ergonomics. This study was registered on Clinical Research Information Service (CRIS) registry (KCT0006948). Methods Fifty operators with varying levels of experience were enrolled to intubate an airway mannequin at two different bed heights— anterior superior iliac spine (level A) and xyphoid process (level X) of each operator—in a randomized sequence. The laryngoscopy force measured with a Pliance® pressure sensor attached to the surface of the Macintosh laryngoscopy blade, intubation characteristics, and ergonomic score based on the Rapid Entire Body Assessment tool were compared between the two bed heights (level A vs. X). Results Peak and impulse laryngoscopy forces were significantly lower at xyphoid (level X) compared to the lower bed height (level A) (peak force: 36.06 ± 9.77 N vs. 33.74 ± 8.69 N, P = 0.049; impulse force: 251.82 ± 106.06 N vs. 224.18 ± 86.48, P = 0.005). Laryngeal view (Cormack-Lehane grade) and subjective comfort were also better at level X (P = 0.0024 and P < 0.001, respectively). The ergonomic score was higher at the lower bed height (level A, P < 0.001), indicating a more strenuous work posture. Conclusion Bed height at xyphoid level reduced laryngoscopy force while improving laryngeal view and ergonomic comfort compared to ASIS level. Adjusting the bed height before endotracheal intubation can improve the operating environment, which in turn may contribute to safety of both patient and operator.